Methodology for evaluation of entrepreneurial training - Krstić Milan; Skorup Ana; Lapčević Goran (Trendovi u Poslovanju)
Entrepreneurship is a field of practical action by people that integrates their ability to first discover the prospective business opportunities from the environment, then select the one that by their criteria is the most promising, then accept the risk and provide the necessary conditions for its realization, and finally to persist on the sustainability of the initiated entrepreneurial venture. In order to stimulate the development of entrepreneurship, especially in the case of people who start their own entrepreneurial venture, and in order to reduce the risk of failure, it is necessary to design appropriate entrepreneurial training. As a rule, the program of entrepreneurial training includes motivational training, training for the development of creative ideas, training in the preparation of a business plan, as well as training for its successful presentation. Here, from the standpoint of its effectiveness, the following key questions are raised: is it possible and to what extent to be evaluated the delivered entrepreneurial training in terms of learned as well as the commitment to undertake their own entrepreneurial venture? In this paper, the methodology developed for this purpose is presented in a shortened scope. The basic methodology is the standard Kirkpatrick model that consists of four levels of evaluation. Due to the specificity of the phenomenon, which is evaluated on this occasion, the model is specifically adapted to the evaluation of entrepreneurial training. The methodology is based on the survey of entrepreneurial knowledge and attitudes of the participants before and after the entrepreneurial training, as well as the subsequent analysis in order to anticipate the realized entrepreneurial effects.